Genome-Wide Identification and Characterization of GARP Transcription Factor Gene Family Members Reveal Their Diverse Functions in Tea Plant (Camellia sinensis) - Yue, Chuan; Chen, Qianqian; Hu, Juan; Li, Congcong; Luo, Liyong; Zeng, Liang (Frontiers in Plant Science, 2022)
Golden2, ARR-B, Psr1 (GARP) proteins are plant-specific transcription factors that play vital and diverse roles in plants. However, systematic research on the GARP gene family in plants, including tea plant (Camellia sinensis), is scarce. In this study, a total of 69 GARP genes were identified and characterized from the tea plant genome based on the B-motif sequence signature. The CsGARP genes were clustered into five subfamilies: PHR1/PHL1, KAN, NIGT1/HRS1/HHO, GLK and ARR-B subfamilies. The phylogenetic relationships, gene structures, chromosomal locations, conserved motifs and regulatory cis-acting elements of the CsGARP family members were comprehensively analyzed. The expansion of CsGARP genes occurred via whole-genome duplication/segmental duplication, proximal duplication, and dispersed duplication under purifying selective pressure. The expression patterns of the CsGARP genes were systematically explored from various perspectives: in different tissues during different seasons; in different leaf color stages of tea plant; under aluminum treatment and nitrogen treatment; and in response to abiotic stresses such as cold, drought and salt and to biotic stress caused by Acaphylla theae. The results demonstrate that CsGARP family genes are ubiquitously expressed and play crucial roles in the regulation of growth and development of tea plant and the responses to environmental stimuli. Collectively, these results not only provide valuable information for further functional investigations of CsGARPs in tea plant but also contribute to broadening our knowledge of the functional diversity of GARP family genes in plants.